Organizational values and its relevance in the performances of healthcare sector - Dhwany DB; Dr. Amit Kansal Kansal (International Journal of Educational Technology Research, 2023)
Abstract Values are the conceptual framework of an organization. It reveals the intentions, directions, and structures of services to be given for the customers. An organization cannot be connected with the customers / community unless it has not been defined with values especially in healthcare sector. The performances of healthcare sector are complex in nature due to the combination features of various services like medical, administrative, technical, supportive and human relations for meeting physical and mental wellbeing of customers. As the field of dependence increases, the complexity of interaction also increases. The combined efforts in services have to be coordinated very well in association with values; otherwise, the relevance of organizational values will be affected with the performances, which will lead to customer dissatisfaction. This study rationally reviews and analyses such scenarios in the healthcare sector. Several strategic/ technological platforms are used in healthcare sector for supporting various dimensions of activities. The major challenge is the identification of suitable platform in relation with the values of the organization. Balanced score card is used to quantify the values and these values are used to analyse the association with performance measures. Observations: Most of the organizations have failed to identify the causative and responsive features behind the technological platform. They were not able to relate the practices in the technological platform and the values followed by the organizations. Such pitfalls are able to make distributive failures in values within the system. Conclusion: To reach highest level of performance (performance optimization), the activities and services have to be in consensus with the values of the organization. Key words :